Assessment of caregiving burden among caregivers of older adults with stroke in Saudi Arabia: analytical cross-sectional study - Ala’a Alahmadi; Sami A R Al-Dubai; Rana A. Alhelali; Hamadi A. Alrefaei; Nader M. Alqerafi (BMC Public Health)
Abstract Background Stroke is a prominent contributor to disability on a global scale, and individuals who care for patients with stroke frequently face substantial challenges. Identifying the precise elements contributing to the burden of care is crucial to provide valuable insights for creating focused interventions and support programs to assist caregivers. Hence, the aim of conducting the study was to measure the caregiving burden among caregivers of older adults with stroke in Al-Madinah. Method An analytical cross-sectional study was conducted in home healthcare centers in Al-Madinah, Saudi Arabia, from March 2024 to December 2024. The participants were caregivers of patients with stroke selected using a random cluster sampling technique. The Zarit Caregiver Burden Inventory was used to measure the severity of the caregiver burden. Latent profile analysis (LPA) was used to stratify caregivers into distinct subgroups. Multivariable log-binomial regression examined the adjusted association between the likelihood of high caregiver burden and sociodemographic features of patients and caregivers. Results Of the 264 caregivers, the mean age was 40.7; 81.8% were female; 63.3% belonged to class I, “high caregiver burden”; and 36.7% belonged to class II, “low caregiver burden.” Patient factors associated with a higher probability of being in class I were paralysis (PR = 10.81) and trouble walking (PR = 6.70). Conversely, caregivers of patients who were 60–69 years old (PR = 0.43) and had three or fewer comorbidities (PR = 0.11) were less likely to fall into class I. Caregivers’ characteristics associated with a lower probability of being in the class I were having a college degree or higher (PR = 0.27) and employing paid care (PR = 0.27). Conclusion The study revealed that a significantly high caregiving burden was linked to patients’ advanced age, multiple comorbidities, and the presence of paralysis or difficulty walking. Additionally, caregivers’ socioeconomic status was associated with a high caregiving burden. Implementing supporting programs for family caregivers of patients with stroke is crucial for enhancing patient outcomes and reducing the financial strain on the healthcare system. Consider them an integral part of the care team, as their unpaid caregiving helps improve the efficiency and effectiveness of care.